ENTRE O IDÍLIO DE OUTRORA E O ACENO AO FUTURO: A história do fim do jornal impresso O Estado do Maranhão - OLIVEIRA NETO, Otávio Temóteo de (2024)
From the end of the 20th century and the beginning of the 21st century, the internet enabled a new model of integration between printed periodicals and digital newspapers, which generated numerous discussions about the implications of the end of print and the advent of digital newspapers. It is within this framework of transitions that we present our objective: the end of the newspaper O Estado do Maranhão. From this, our fundamental question arises: how did the newspaper O Estado do Maranhão tell readers the end of its printed version, in what we call the dramatic project of O Estado do Maranhão? Among the specific objectives, we verified: a) how the newspaper built an identity about itself to narrate its ending; and b) what narrative/dramatic project is used by the newspaper as an institutional enunciator interested in convincing the public and readers. In this work, we propose to study the narrative about the end of the newspaper O Estado do Maranhão based on the material narrated in the last printed edition of the periodical. The situation of communication in presentia makes it clear that we start from the newspaper's own way of narrating, its speech acts and its official positioning. We considered the corpus to support this research, all editorials and articles from the last printed version that circulated on 10/23/2021. The methodology chosen for the work is the Pragmatic Analysis of Journalistic Narrative designed by Luiz Gonzaga Motta (2013) in line with the narrative studies developed by Ricoeur (2010). This interpretative perspective of the narrative is in line with the theoretical foundations mobilized in this work, which weighs on the operational, hermeneutic and interpretative function of the newspaper O Estado do Maranhão. The methodology works as an interpretative tool for a concrete, historically situated process that involves revealing processes outside the discourse itself, anchored in the interpretation of the narrative of the factual world from the end of the printed matter studied. As the main results of the research, we can highlight that the newspaper O Estado do Maranhão omitted from the public and readers the reason for the end of print, built an identity throughout the last edition in order to reinforce the role of technology from the past to the future of the periodical, the construction of identity in the last edition followed the narrative focus of what the newspaper was interested in recording only positive points as a historical mark of the newspaper, and finally, the dominant point of view of the discourse and story plan of the last edition is the point from an institutional point of view through a narrative frame or dramatic project that aimed to intuit readers and the public that the main responsible for the end of print was the advent of technology.